MINAT SISWA TERHADAP SENI TARI DALAM KEGIATAN EKSTRAKURIKULER TARI DI SMP PEMBANGUNAN LABORATORIUM UNP - Fitris Fitris; Fuji Astuti; Zora Iriani (SENDRATASIK UNP, 2018)
Abstract This article aims to discover and describe the Interest of students Towards the art of dance in Dance in JUNIOR HIGH SCHOOL extracurricular activities Development Laboratory research using the UNP. qualitative method with descriptive analysis approach. The object of this research is the students who follow the Extracurricular dance in JUNIOR Development Laboratory UNP totalling 18 people. Research instrument this is a researcher as observer and tools in accordance with observation sheets. The technique of data collection on penilitian this is with the study of librarianship, documentation, observation, and then processed using the formula percentages and rates close to the respondent. The results showed that the interest of students towards extracurricular dance belongs to the medium. It is obtained from the results of the calculations of the indicator by using the observation sheets feeling pleased with the amount of percentage of 70.3% 55.5%, interest, attention to 62.9%, 75.9% engagement, curiosity 46.2% and 33.3% of the needs. So the summation of the data obtained through observation is 57.4%.Keywords: Interest students, dance art, extracurricular activities